PENGARUH DISIPLIN KERJA TERHADAP KUALITAS PELAYANAN DI UPTD PUSKESMAS RAWAT INAP CONGGEANG KABUPATEN SUMEDANG - Maisyaroh, Fuji Dwi (LPPM UNSAP & FISIP UNSAP, 2025)
ABSTRACT THE EFFECT OF WORK DISCIPLINE ON SERVICE QUALITY AT UPTD INPATIENT HEALTH CENTER CONGGEANGSUMEDANG REGENCY Fuji Dwi Maisyaroh The purpose of this study was to determine Work Discipline and Service Quality, to determine the relationship between Work Discipline and Service Quality and to determine the magnitude of the influence of Work Discipline on Service Quality at UPTD Inpatient Health Center Conggeang Sumedang Regency. This study uses a descriptive analysis method with a quantitative approach. The variables of this study use variables that will be measured from a free variable of work discipline and a dependent variable of service quality. The population used in this study were all employees at UPTD Inpatient Health Center Conggeang Sumedang Regency, totaling 75 employees and all samples were taken totaling 75 people. The methods used were literature study, field study (questionnaire, observation). Based on the results of the study, it is known that Work Discipline at the Conggeang Inpatient Health Center UPTD, Sumedang Regency is in the very good criteria with an analysis result of 85.9%. Then for the Quality of Service at the Conggeang Inpatient Health Center UPTD, it is in the very good criteria with an analysis result of 97.0%. From the results of the correlation analysis, a correlation value of 0.811 was obtained, which indicates a positive and significant relationship between Work Discipline and Service Quality at the Conggeang Inpatient Health Center UPTD, Sumedang Regency. From the results of the significance test, a value greater than 11.84> 1.993 was obtained. From the results of the determination coefficient analysis, it is known that Work Discipline at the Conggeang Inpatient Health Center UPTD, Sumedang Regency is influenced by Service Quality by 65.7% while the side of 34.3% is influenced by other factors outside the study (epsilon factor). Keywords: Work Discipline, Service Quality